ВЗАЄМОДІЯ МІКРООРГАНІЗМІВ З ГЛИНИСТИМИ МІНЕРАЛАМИ ЯК ОСНОВА СТВОРЕННЯ ГРАНУЛЬОВАНИХ БАКТЕРІАЛЬНИХ ПРЕПАРАТІВ КОМПЛЕКСНОЇ ДІЇ ДЛЯ РОСЛИННИЦТВА - Курдиш , І.К.; Гордієнко , А.С. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2007)
Regularities of bacteria interaction with clay minerals are ana¬lysed in the article. There are discussed the mechanisms of stimulation of physiological activity of nitrogen-fixing and phosphate-mobilizing bacteria, on the basis of which the granulated microbial preparation of complex action on plants have been created. These preparations impro¬ve plant development and increase their productivity essentialy.